El Psicólogo: Sombra y Alimento del Pueblo (Hacía una Psicología integral) - Chiappo, Leopoldo (1993)
The author presents the delicate and important role that psychologists play in the social community, trying to go beyond the dogmatic view of psychologists as conduct technologists. He proposes a Holistic Psychology which considers it as a discipline that uses scientific, as well as humanistic, artistic, literary, philosophical and theological knowledge.